Wide Disagreement Between Alternative Assessments of Premorbid Physical Activity: Subjective Patient and Surrogate Reports and Objective Smartphone Data. Issue 10 (October 2017) - Gluck, Samuel; Summers, Matthew J.; Goddard, Thomas P.; Andrawos, Alice; Smith, Natalie C.; Lange, Kylie; Iwashyna, Theodore J.; Deane, Adam M.
Abstract : Objectives: Surrogate-decision maker and patient self-reported estimates of the distances walked prior to acute illness are subjective and may be imprecise. It may be possible to extract objective data from a patient's smartphone, specifically, step and global position system data, to quantify physical activity. The objectives were to 1) assess the agreement between surrogate-decision maker and patient self-reported estimates of distance and time walked prior to resting and daily step-count and 2) determine the feasibility of extracting premorbid physical activity (step and global position system) data from critically ill patients. Design: Prospective cohort study. Setting: Quaternary ICU. Patients: Fifty consecutively admitted adult patients who owned a smartphone, who were ambulatory at baseline, and who remained in ICU for more than 48 hours participated. Measurments and Main Results: There was no agreement between patients and surrogates for all premorbid walking metrics (mean bias 108% [99% lower to 8, 700% higher], 83% [97% to 2, 100%], and 71% [96% to 1, 080%], for distance, time, and steps, respectively). Step and/or global position system data were successfully extracted from 24 of 50 phones (48%; 95% CI, 35–62%). Surrogate-decision makers, but not patient self-reported, estimates of steps taken per day correlated with smartphone data (surrogates: n = 13, ρ = 0.56, p < 0.05; patients: n = 13, ρ = 0.30, p = 0.317). Conclusion: There was a lack of agreement between surrogate-decision maker and patient self-reported subjective estimates of distance walked. Obtaining premorbid physical activity data from the current-generation smartphones was feasible in approximately 50% of patients. Abstract : Supplemental Digital Content is available in the text.